2022
DOI: 10.13057/biodiv/d230253
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and composition of butterflies in three habitats around Rayow Waterfall, Minahasa District, North Sulawesi, Indonesia

Abstract: Abstract. Koneri R, Nangoy MJ, Maabuat PV, Saroyo, Wakhid. 2022. Diversity and composition of butterflies in three habitats around Rayow Waterfall, Minahasa District, North Sulawesi, Indonesia. Biodiversitas 23: 1091-1098. Butterflies play an important role in ecosystems as pollinating agents, and their beautiful colors have a high potential for ecotourism activities. This study aims to analyze the diversity and composition of butterflies on three habitats around Rayow Waterfall, Minahasa District, North Sulaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
2
Order By: Relevance
“…The biplot analysis results showed that there was no water source at this altitude, but it had high temperature and humidity, a lack of forage plants, and a fairly dense canopy cover. According to Koneri et al [28] stated that butterflies prefer habitats with moderate temperature. This is in line with Alarape et al [29], who reported that temperature can affect oviposition, mating behavior, larval development, and butterfly food plants.…”
Section: Discussionmentioning
confidence: 99%
“…The biplot analysis results showed that there was no water source at this altitude, but it had high temperature and humidity, a lack of forage plants, and a fairly dense canopy cover. According to Koneri et al [28] stated that butterflies prefer habitats with moderate temperature. This is in line with Alarape et al [29], who reported that temperature can affect oviposition, mating behavior, larval development, and butterfly food plants.…”
Section: Discussionmentioning
confidence: 99%
“…El área del Parque Turístico Aik Bukak se registraron 327 individuos pertenecientes a 23 especies, 18 géneros y 5 familias (Ashari et al, 2021). Otro estudio similar se realizó en la Cascada Rayow en Indonesia, registrando un total de 943 individuos, pertenecientes a 56 especies y 5 familias (Koneri et al, 2022). Estudios han demostrado que, el conocimiento ecológico local de la diversidad de mariposas se deriva de propósitos utilitarios actuales, como vender mariposas como souvenirs a los turistas (Yang et al, 2022).…”
Section: Lepidópteros Como Especies Carismáticasunclassified
“…En términos de riqueza de especies, las mariposas se encuentran entre los grupos de fauna con más especies del mundo. Estas especies juegan un papel importante en los ecosistemas como agentes polinizadores, y sus hermosos colores tienen un alto potencial para las actividades de ecoturismo (Koneri et al, 2022).…”
Section: Introductionunclassified
“…There are approximately 18,000 described butterfly species in the world [19], with about 90% found in the tropics [20], making the tropical region an important area for butterfly conservation [21]. Butterflies frequently need resources available in healthy ecosystems, such as flowers for nectar; specific host plants that caterpillars can use as a food source; and bare, moist soil patches for water and salts [22].…”
Section: Introductionmentioning
confidence: 99%